Mental Predicate Feel Subtype Feel and Think in Japanese: A Natural Semantic Metalanguage Approach - Ratnayanti Sukma, Luh Putu; Netra, I Made (e-Journal of Linguistics, 2019)
According to Goddard and Wierzbicka (2014) the original meaning of the mental predicate consists of six types namely, think , know , feel , see , hear , want and don't want . This finding was then forwarded to Japanese by Asano Cavanagh (2015), finding 12 verbs of Japanese language conditions that are matched with those found by Goddard and Wierzbicka (2014). Of the twelve state verbs that were passed on by Asano, the type FEEL was matched with the mental predicate ??? kanjiru . Mental predicate??? kanjiru has a subtype which turns out to produce more mental predicate than the other six types. Found subtypes FEEL and THINK, FEEL and HAPPEN, FEEL and DO, FEEL and TELL. Subtype FEEL and THINK produces 2 sub-subtypes namely FEEL and THINK (GOOD) and FEEL and THINK (BAD). Keywords: mental predicate, feel, type, subtype